THE COVID-19 VACCINE: MYTHS AND FACTS IN POPULATION OF PAKISTAN - Dr. Farheen Shaikh, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
The development of COVID-19 vaccine has been created nuisance and propaganda not only in Pakistan but globally. The big public issue is whether to get vaccine or not. In Pakistan illiteracy rate is high. The myths and absurd concept is already present in their thoughts; therefore, it is hard for the government of Pakistan to vaccine whole population. It is very important to aware the population of Pakistan about the vaccine by separating the myths from facts. 1 The Myth about COVID-19 vaccine is that it is unsafe, because it was developed so fast and rapidly. The fact is COVID-19 vaccine boostsimmune system of the human body to make spike protein, which are found on the surface of coronavirus.2 The Myth about COVID-19 vaccine is it effects on fertility. This Misperception arose on social media that syncitin-1 spike protein, which is same protein present on the coronavirus. The spike protein, syncitin-1 that attached on placenta and responsible for the development of placenta during pregnancy. Fabricated report create misconception that pregnant women getting the vaccine would affect her fertility due to development of spike protein